Preparation method of carbon-coated lithium iron phosphate

By adding P2O5 to absorb carbonized water during the preparation of carbon -covered iron phosphate, and carbonized under low temperature vacuum conditions, the problem of carbon source carbonization generated the problem of gases to damage the uniformity of the carbon covering layer, which improved the materials Electrochemical properties and structural stability.

CN119370820APending Publication Date: 2025-01-28YIBIN TIANYUAN NEW LITHIUM BATTERY CO LTD

Patent Information

Application Number
CN202411540000.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the existing preparation methods for carbon-coated lithium iron phosphate, the carbonization process of the carbon source generates a large amount of gas, destroying the uniformity of the carbon coating layer and affecting the performance of the material.

Method used

Add P2O5 to the front -wheel drive body, use its excellent water absorption performance to absorb water produced by carbon sources, avoid water vapor production, and carbonize under low temperature vacuum conditions to ensure that P2O5 fully absorbs water and prevent gas from getting out of the gas.

Benefits of technology

It improves the uniformity of carbon covering layer, enhances the attachment capabilities of carbon on the surface of lithium iron phosphate particles, improves the electronic conductivity and charging and discharge performance of the material, while reducing the effects of energy consumption and high temperature on the structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370820A_ABST
    Figure CN119370820A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of carbon-coated lithium iron phosphate, which comprises the following steps: mixing, grinding and spray-drying raw materials to obtain a precursor, then mixing the precursor, P2O5, nano iron oxide red and lithium carbonate in a mass ratio of 100: (5-20): (2-8): (3-12), performing vacuum low-temperature carbonization, and then performing high-temperature sintering to obtain the carbon-coated lithium iron phosphate, according to the invention, the dehydration effect of P2O5 is utilized to absorb water generated by carbonization of a carbon source, so that the generation of water vapor is avoided, the adhesive ability of carbon on the surfaces of lithium iron phosphate particles is improved, the uniformity of a carbon coating layer is ensured, and the carbon coating effect is improved; the proportion of the amount of the precursor, P2O5, nano iron oxide red and lithium carbonate is controlled, so that the proportion of lithium, iron and phosphorus in the carbon-coated lithium iron phosphate is strictly matched, and the structural stability of the carbon-coated lithium iron phosphate is ensured; meanwhile, the carbonization temperature is reduced, the energy consumption is reduced, and the performance of the carbon-coated lithium iron phosphate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron phosphate preparation, and more specifically, to a method for preparing carbon-coated lithium iron phosphate. Background Art

[0002] In the field of lithium battery manufacturing technology, lithium iron phosphate is an important positive electrode material, and its performance directly affects key performance indicators such as the battery's energy density, power density and cycle life. However, lithium iron phosphate has low electronic conductivity, which affects the battery's rate performance and hinders its electrochemical performance. In order to improve the electrochemical performance of lithium iron phosphate, some researchers have increased its conductivity by removing residual moisture from the lithium iron phosphate material.

[0003] For example, the invention patent with publication number CN101604749A discloses a method for improving the conductivity of lithium iron phosphate positive electrode material, which is specifically as follows: (1) weighing iron source, phosphate source and lithium source respectively, mixing and adding acetone, with the volume ratio of iron source to material being 1.8:1 to 2.2:1, and stirring thoroughly until there are no bubbles; (2) ball milling the dried sample at a speed of 500 per minute for 8 to 12 hours, and the particle diameter is less than 5 microns; (3) baking the ball milled sample in air at 108°C for 8 to 12 hours to obtain lithium iron phosphate material; (4) placing the dried sample in a high-temperature furnace, calcining at 300°C to 400°C for 2.5 to 3.5 hours in an ordinary pure nitrogen atmosphere, and calcining at 550°C to 650°C for 5 to 7 hours, wherein the residual moisture in the lithium iron phosphate material is removed by introducing a dehydrating gas, vacuum pumping water and phosphorus pentoxide, thereby greatly improving its conductivity and achieving a capacity of more than 160 mAh / g.

[0004] In addition, researchers usually perform carbon coating on the surface of lithium iron phosphate to improve its electronic conductivity. At present, the main method of carbon coating is to mix a carbon source with lithium iron phosphate, and then carbonize the carbon source by high-temperature sintering to form a carbon coating. However, the existing carbon coating technology mainly forms a carbon coating by coating an organic carbon source on the surface of lithium iron phosphate and then carbonizing the carbon source by high-temperature heat treatment. Although this method can improve the electronic conductivity of lithium iron phosphate, the carbonization process of the carbon source often requires a higher temperature, which will lead to increased energy consumption and may also affect the structural stability of lithium iron phosphate. It is difficult for carbon to form a uniform carbon coating on the surface of lithium iron phosphate particles, which has limited improvement in the conductive behavior of lithium iron phosphate and affects its electrochemical performance. In addition, a large amount of gas will be generated during the carbonization of the carbon source, which may destroy the uniformity of the carbon coating and affect the effect of carbon coating.

[0005] In order to improve the electrochemical performance of carbon-coated lithium iron phosphate, some studies have been conducted to achieve this by doping. For example, the invention patent with publication number CN117374242A discloses a method for preparing nitrogen-sulfur co-doped carbon-coated lithium iron phosphate using starch as a carbon source. The method is to place a certain mass of starch by-product in a thiourea solution, soak it fully, place it in a ball mill after drying, and perform mechanical ball milling. After ball milling for a period of time, solid phosphorus pentoxide is added, and the starch by-product particles are refined by adjusting the ball milling time and ball milling speed process parameters. The starch by-product particles are used as a coating modification material, and the mixture is ground and mixed with iron phosphate and a lithium source, and then calcined under inert gas protection to obtain a carbon-coated lithium iron phosphate material. The method dopes nitrogen, phosphorus, and sulfur atoms, introduces more active sites, changes the electronic structure of carbon, enhances its conductivity, and thus has excellent electrochemical properties. The phosphorus pentoxide is used as a phosphorus atom dopant.

[0006] Some researchers have also improved the electrochemical performance by improving the uniformity of carbon coating. For example, Chinese patent CN102683702A discloses a method for preparing lithium iron phosphate with uniform carbon coating on the surface, which includes the following steps: (1) placing organic matter, iron phosphate and lithium source compound in a high-energy ball mill, adding an organic solvent, and performing wet ball milling; (2) low-temperature pretreatment: placing the mixture in an atmosphere furnace, under the protection of a non-oxidizing atmosphere, heating the mixture from room temperature to 140-180°C at a rate of 2-5°C / min, and keeping the temperature for 0.5-2 hours; (3) dehydration Condensation polymerization: heating the temperature to 600-800°C at a heating rate of 5-10°C / min and calcining for 5-15 hours; in the low-temperature pretreatment step of this method, the organic matter is melted into a liquid at a low temperature, and can be dehydrated and condensed at a higher temperature, wherein the organic matter is completely melted and presents a fluid state, which is easy to spread on the surface of adjacent solid particles to form a uniform coating layer. During the dehydration and condensation, the condensation polymer is tightly coated on the surface of the solid particles, which is not only beneficial to the reduction process of trivalent iron, but also conducive to the formation of a close interaction between lithium iron phosphate and the coated carbon, thereby improving the uniformity of the carbon coating.

[0007] In summary, the prior art has not noticed that the large amount of gas generated during the carbonization process of the carbon source will affect the uniformity of the carbon coating layer, thereby affecting the performance of the carbon-coated lithium iron phosphate. Summary of the invention

[0008] In view of the above, the present invention provides a method for preparing carbon-coated lithium iron phosphate, which effectively solves the problem that a large amount of gas generated by carbonization of the carbon source destroys the uniformity of the carbon coating layer during the preparation of the carbon-coated lithium iron phosphate, thereby improving the effect of carbon coating.

[0009] The present invention provides a method for preparing carbon-coated lithium iron phosphate, comprising preparing lithium iron phosphate raw materials, grinding and spray drying to obtain a precursor, then adding P2O5, nano red iron oxide and lithium carbonate to the precursor, mixing them evenly, performing vacuum carbonization, and finally performing high-temperature sintering to finally obtain the carbon-coated lithium iron phosphate.

[0010] The mass ratio of the precursor, P2O5, nano iron oxide red and lithium carbonate is 100:5-20:2-8:3-12.

[0011] Among them, preferably, the mass ratio of the precursor, P2O5, nano red iron oxide and lithium carbonate is 100:5-15:2-6:3-9.

[0012] The temperature of vacuum carbonization is 100-200°C, and the time is 2-4 hours.

[0013] The raw materials for preparing carbon-coated lithium iron phosphate include iron phosphate, lithium carbonate, glucose, polyethylene glycol, etc. Among them, carbon-containing compounds such as glucose as a carbon source will gradually decompose as the temperature rises during the preparation process of carbon-coated lithium iron phosphate to generate gases such as water vapor and CO. The gases are fluid, and when they escape to the outside of the particles, the adhesion ability of the carbon on the surface of the particles will be reduced, the uniformity of the carbon coating layer will be destroyed, and the effect of carbon coating will be adversely affected. Therefore, the present invention adds P2O5 to the precursor, and utilizes the excellent water absorption performance of P2O5 to absorb the water generated by the carbonization of the carbon source at the first time, thereby avoiding the generation of water vapor and improving the adhesion ability of carbon on the surface of lithium iron phosphate particles.

[0014] Since P2O5 generates phosphoric acid after absorbing water, the present invention adds nano red iron oxide and lithium carbonate to the precursor while adding P2O5 to adjust the ratio of lithium, iron and phosphorus in the carbon-coated lithium iron phosphate; the dehydration amount of the carbon source is obtained by thermogravimetric analysis, and the addition amounts of P2O5, nano red iron oxide and lithium carbonate are calculated according to the dehydration amount of the carbon source. Therefore, the present invention adds the precursor, P2O5, nano red iron oxide and lithium carbonate in a mass ratio of 100:5-20:2-8:3-12 to ensure that the ratios of lithium, iron and phosphorus in the carbon-coated lithium iron phosphate are strictly matched.

[0015] At the same time, after adding P2O5, nano-iron oxide red and lithium carbonate to the precursor, vacuum low-temperature carbonization is carried out to make the carbon source carbonized at low temperature, ensuring that P2O5 can fully absorb the water generated by the carbonization of the carbon source, avoiding the water generated due to the violent reaction before being absorbed and escaping as water vapor, thereby ensuring the uniformity of the carbon coating layer, and under vacuum conditions, the generation of carbon oxides such as CO can be effectively avoided, further reducing the influence of gas on carbon coating.

[0016] Beneficial effects of the present invention: (1) By adding P2O5 to the precursor, the dehydration effect of P2O5 is utilized to absorb the water generated by the carbonization of the carbon source, thereby avoiding the generation of water vapor, improving the adhesion ability of carbon on the surface of lithium iron phosphate particles, ensuring the uniformity of the carbon coating layer, and improving the carbon coating effect; (2) By matching the dehydration amount of P2O5 and the carbon source, the ratio of the precursor, P2O5, nano-iron oxide red and lithium carbonate is controlled to ensure that the ratio of lithium, iron and phosphorus in the carbon-coated lithium iron phosphate is strictly matched, thereby ensuring the structural stability of the carbon-coated lithium iron phosphate; (3) By vacuum carbonizing the precursor, P2O5, nano-iron oxide red and lithium carbonate at low temperature, not only the temperature required for carbon source carbonization is reduced, reducing energy consumption, but also ensuring that P2O5 can fully absorb the water generated by carbonization of the carbon source, avoiding the escape of water vapor, and effectively avoiding the generation of carbon oxides such as CO, ensuring the uniformity of the carbon coating layer, and avoiding the influence of high temperature on the structural stability of carbon-coated lithium iron phosphate; (4) The present invention improves the electronic conductivity and charge-discharge performance of the carbon-coated lithium iron phosphate material, and the process is simple, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the carbon-coated lithium iron phosphate prepared in Example 1 of the present invention.

[0018] Figure 2 This is a SEM image of the carbon-coated lithium iron phosphate prepared in Example 2 of the present invention.

[0019] Figure 3 This is a SEM image of the carbon-coated lithium iron phosphate prepared in Example 3 of the present invention.

[0020] Figure 4 It is a SEM picture of the carbon-coated lithium iron phosphate prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The embodiments of the present application will be described in more detail below. The application can be implemented in various forms, and should not be construed as being limited to the embodiments set forth herein, but rather these embodiments are provided to provide a more thorough and complete understanding of the present application. It should be understood that the embodiments of the present application are only for exemplary purposes and are not intended to limit the scope of protection of the present application.

[0022] The embodiments of the present invention are implemented with the following technical solutions: (1) iron phosphate, lithium carbonate, glucose, and polyethylene glycol were mixed in a mass ratio of 80:20:5:4, and then ground in a ball mill for 4 hours at a rotation speed of 500 rpm. After grinding, the material was spray-dried at a drying temperature of 200° C. for 2 hours to obtain a precursor; (2) Add P2O5, nano-iron oxide red and lithium carbonate to the precursor. The mass ratio of the precursor, P2O5, nano-iron oxide red and lithium carbonate is 100:5-20:2-8:3-12, and then treat it under vacuum and at a temperature of 100-200°C for 2-4 hours, and finally sinter it at a temperature of 700°C for 10 hours in an argon atmosphere, and then cool it to room temperature to obtain carbon-coated lithium iron phosphate.

[0023] Table 1 shows the specific implementation conditions and electrochemical performance test results of the embodiments and comparative examples of the present invention. It can be seen that when the mass ratio of the precursor, P2O5, nano-red iron oxide and lithium carbonate is 100:5:2:3, the performance of the prepared carbon-coated lithium iron phosphate material is the best, and the performance of the carbon-coated lithium iron phosphate material prepared in the comparative example without adding P2O5, nano-red iron oxide and lithium carbonate is greatly improved, and its powder resistance, compaction density, 0.1C discharge capacity and first efficiency are significantly improved. At the same time, Figure 1 and Figure 4 The SEM images of the carbon-coated lithium iron phosphate prepared in Example 1 and the comparative example respectively show that Figure 1 The flocculent matter between particles is relatively Figure 4 There are fewer flocculent substances between the particles; therefore, the above proves that the method of the present invention can achieve a better carbon coating effect and improve the performance of the carbon-coated lithium iron phosphate material.

[0024] Among them, with the increase of the addition amount of P2O5, nano iron oxide red and lithium carbonate, some properties of the prepared carbon-coated lithium iron phosphate are reduced. This is because it is affected by the iron content. In the case of moderate iron excess, slightly more iron vacancies are formed, which helps to improve the conductivity. However, if the iron content exceeds the ideal stoichiometric ratio, it may cause changes in the structure and composition of the material, affecting the number of lithium ions embedded and extracted, thereby reducing the actual capacity and conductivity of the battery. However, Figure 2 and Figure 3 It can be seen that the flocculent substances between the particles of the carbon-coated lithium iron phosphate material prepared by adding P2O5, nano-iron oxide red and lithium carbonate are relatively Figure 4 There are fewer flocculent materials between the particles, which means that although the increase in iron content affects some properties of the carbon-coated lithium iron phosphate material, a better carbon coating effect can still be achieved, and the compaction density of the carbon-coated lithium iron phosphate material is improved.

[0025] Table 1: Specific implementation conditions and electrochemical performance test results of the embodiments of the present invention and comparative examples.

[0026] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in this application, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing carbon-coated lithium iron phosphate, comprising obtaining a precursor by raw material batching, grinding and spray drying, and then sintering the precursor at high temperature to obtain carbon-coated lithium iron phosphate, characterized in that: P2O5, nano red iron oxide and lithium carbonate are added to the precursor, mixed evenly, then vacuum carbonized and finally sintered at high temperature to finally obtain carbon-coated lithium iron phosphate.

2. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The mass ratio of the precursor, P2O5, nano red iron oxide and lithium carbonate is 100:5-20:2-8:3-12.

3. The method for preparing carbon-coated lithium iron phosphate according to claim 2, characterized in that: The mass ratio of the precursor, P2O5, nano red iron oxide and lithium carbonate is 100:5-15:2-6:3-9.

4. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The vacuum carbonization temperature is 100-200° C. and the time is 2-4 hours.

Citation Information

Patent Citations

  • Method for improving electric conductivity of lithium iron phosphate battery anode material

    CN101604749A

  • Preparation method of lithium iron phosphate with surface being uniformly coated by carbon

    CN102683702A

  • Nitrogen, phosphorus and sulfur co-doped biomass carbon coated modified lithium iron phosphate material and preparation method thereof

    CN117374242A

Cited By

  • High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof

    CN120664513A